State, Industries and Regulation in Nigeria: Ife Iron and Steel Company and Environmental Pollution (Journal of Management and Social Sciences, 2020)
Discourse on environmental pollution in Nigeria has often revolved around the environmental impacts of the operations of multinational oil companies in Nigeria’s Niger Delta. However, experience has shown that other regions of the country also contend with pollution problems. Informed by this position, this study examines environmental pollution associated with the activities of Ife Iron and Steel Nigeria Limited, which is located in Osun State. The study makes use of empirical data that comprises of unstructured in-depth interviews, observation, and an interview conducted by a media house (Channels Television Station, Lagos). The data was analysed using the thematic approach. Results from fieldwork revealed that pollution from operations of Ife Iron and Steel Company are sources of concern to communities in the vicinity of its location. It is reported that soot and other particles emitting from the company’s operations are harmful to the health of the residents and undermine their sources of livelihood. Informed by its findings, this paper argues that without effective enforcement of environmental regulations in Nigeria, people’s health and livelihood will continue to be adversely affected by the negativities arising from industrial operations.KeywordsEnvironment, Air Pollution, Regulations, Iron and Steel Industries, Ile-Ife, Nigeria